The relation between fibrinogen level, neutrophil activity and nucleosomes in the onset of disseminated intravascular coagulation in the critically ill. (9th July 2021) - Müller, Marcella C.A.; Dujardin, Romein W.G.; Thachil, Jecko; van Mierlo, Gerard; Zeerleder, Sacha S.; Juffermans, Nicole P.
Abstract: Background: Nucleosomes and neutrophil extracellular traps (NETs) are important in the pathophysiology of disseminated intravascular coagulation (DIC). Fibrinogen, as an acute phase reactant, may be protective by engaging neutrophils. We hypothesize that DIC can occur when NET formation becomes uncontrolled in relation to low fibrinogen levels. Patients/method: The ratio of both circulating nucleosomes and human neutrophil elastase alpha‐1‐antitrypsine complexes (HNE‐a1ATc) to fibrinogen was correlated to thrombocytopenia, DIC and organ failure in 64 critically ill coagulopathic patients. Results: A high nucleosome to fibrinogen ratio correlated with thrombocytopenia and organ failure ( ρ −0.391, p 0.01 and ρ 0.556, p 0.01, respectively). A high HNE‐a1ATc to fibrinogen ratio correlated with thrombocytopenia, DIC and organ failure ( ρ −0.418, p 0.01, ρ 0.391, p 0.01 and ρ 0.477, p 0.01 respectively). Conclusion: These findings support the hypothesis that fibrinogen is protective against DIC by counterbalancing excessive neutrophil activation.